IMPROVING STUDENTS’ READING COMPREHENSION ON DESCRIPTIVE TEXTS BY USING BOOKLETS - Rini, Septia; Y, Y. Gatot Sutapa; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted at the Eighth-Grade students of SMP Negeri 12 Pontianak in academic year 2018/2019 in the form of a classroom action research. The aim of this research was to describe how booklets can improve students’ reading comprehension on descriptive texts. The sample of this research was the students of class VIIIA which consisted of 30 students. The data were collected through observation checklist, field notes, and measurement test. This research was implemented in two cycles. The first cycle involved implementation of booklets with the topics of pet and food. It was found that by making the students explicitly aware of their learning, booklets helped build up good attention and improve students’ reading comprehension. The second cycle involved implementation of booklets with the topics of place and person. This time the students began to link new knowledge with prior knowledge to understand the descriptive text. The researcher provided pictures which illustrated unfamiliar vocabulary to help students understand the content of text. It showed that the students could construct new meaning from the pictures and could comprehend the descriptive texts. In conclusion, the use of booklet could improve students’ reading comprehension. They are now aware of learning and not hesitant to read. Keywords: Reading comprehension, Descriptive Texts, Booklets.